DESENVOLVIMENTO DE CREME ANTISSINAIS A BASE DE ÓLEO DE MORINGA E ÓLEOS ESSENCIAIS - Santos, Neuma Campos Fernandes (2022)
Being popularly known as the “tree of life”, Moringa oleifera is a tree originating in Asia, specifically India, has numerous properties beneficial to human health, in addition to presenting vitamins A, complex B, C, minerals and iron in its leaves. and seeds. The main objective of this study was to develop and evaluate an anti-aging cosmetic cream formulation based on moringa oil, replacing some synthetic ingredients with natural components. A selection of inputs to be used in the formulation was carried out following legislation criteria in accordance with ANVISA. After selection, the formulation was developed and pH, density, color, odor, appearance, stability, microbiological count and product efficacy tests were applied. The microbiological results for the count of total and aerobic mesophilic microorganisms were less than 1000 CFU/g, Pseudomonas Aeruginosa, Staphylococcus aureus, total and fecal coliforms remained absent in 1 g of the sample. The pH remained in an average range of 5.7 throughout the stability study, the density was around 0.99 g/mL and in the efficacy and safety test, the cream obtained excellent results in terms of action on fine lines of expression, with no reports from patients of discomfort or allergy at the site applied, being considered "Dermatologically tested".